Negotiation with Patriarchy in Women's Lives: A Case Study in a Malaysian Public University - Azmawati, Azman Azwan; Endut, Noraida; Mohd Hashim, Intan Hashimah; Selamat, Nor Hafizah; Ying, Kelvin (GATR JOURNALS, 2017)
Objective - While women make up almost 65% of undergraduates in public universities in Malaysia, only in the last three years their labour force participation rates have gone beyond the 50% mark. In addition, women form less than 20% of the legislature and Cabinet of Ministers in Malaysia. What pushes women in their achievements in education and what factors pull them back in other areas? How do patriarchal gender norms underpin their ability and decisions in life's choices and how have they understood and negotiated these norms? This paper aims to explore these questions through narratives of women in a public university.